2011
DOI: 10.1097/prs.0b013e318221dc3e
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Harvesting of a Large Thoracodorsal Artery Perforator Flap with Emphasis on Perforator Number and Spacing

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 0 publications
1
35
0
Order By: Relevance
“…The high inset rate was significantly associated with the development of fat necrosis. Given that excessively large flap transfer can also lead to perfusion‐related complications including partial flap loss in other kinds of perforator flaps, our results seem to be as expected. Too much tissue burden for blood supply by a limited number of perforators can result in a less‐perfused tissue area and fat necrosis.…”
Section: Discussionsupporting
confidence: 78%
“…The high inset rate was significantly associated with the development of fat necrosis. Given that excessively large flap transfer can also lead to perfusion‐related complications including partial flap loss in other kinds of perforator flaps, our results seem to be as expected. Too much tissue burden for blood supply by a limited number of perforators can result in a less‐perfused tissue area and fat necrosis.…”
Section: Discussionsupporting
confidence: 78%
“…Several modified approaches have been described in the literature for large soft tissue defect reconstruction considering primary closure of the donor site. Hwang et al () introduced a chimeric perforator flap to expand the surface of the flap to reconstruct very large wounds, but an additional skin grafting procedure was unavoidable, which resulted in a bulky appearance and unsatisfactory color match. Bigdeli et al () reported that a conjoined parascapular and latissimus dorsi free flap is a large and reliable flap for simultaneous one‐stage reconstruction of complex and unusually large soft‐tissue defects in the knee region.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, recent studies have proposed ALT flaps to be superior to subscapular system flaps (Dayan et al, ; Demirkan et al, ; Demirkan et al, ; Di Candia et al, ; Friji et al, ). Kim et al (Hwang et al, ) aimed to establish potential rationales behind the apparent preference for the ALT over the LD flap (a component of the subscapular system, as listed above). Their study concluded that the limitations of the LD flap were mostly misconceptions; it is not essential to change the position of the patient, a two‐team approach can be used, and the absence of adequate perforators rate was similar to the ALT flap (6.04% in LD vs. 5.4% in ALT) giving no clear objective advantage of the ALT over the LD flap.…”
Section: Discussionmentioning
confidence: 99%